Survey on Image Binarization Techniques for Degraded Document Images - Remya, AR; Azath, M (International Journal of Computer Sciences and Engineering, 2014)
I There are many methods for enhancement of degraded document images. In the process of improving degraded document images segmentation is one of the difficult task due to background and foreground variation such as uneven illumination, document smear such as smudging of text, seeping of ink to the other side of paper, degradation of paper ink due to aging etc. A number of methodologies have been proposed by several researchers on image segmentation using binarization technique. In document analysis, binarization is easily affected by noise, surrounding illumination, gray-level distribution, local shading effects, weak contrast, and the presence of dense non-text components such as photographs. So binarization can become a challenging job under varying illumination and noise. This survey aims to evaluate the principles of image binarization techniques. The main objective of this paper is to evaluate the different image binarization techniques to find the gaps in existing techniques.